For this case we must simplify the following expression:
[tex](12b ^ 2p-3bp ^ 2 + 4bp) + (- 9b ^ 2p-6bp ^ 2 + 5bp) =[/tex]
By law of signs of multiplication we have to:
[tex]+ * - = -\\+ * + = +[/tex]
Rewriting the expression we have:
[tex]12b ^ 2p-3bp ^ 2 + 4bp-9b ^ 2p-6bp ^ 2 + 5bp =[/tex]
We add similar terms:
[tex]12b ^ 2p-9b ^ 2p-3bp ^ 2-6bp ^ 2 + 4bp + 5bp =[/tex]
Equal signs are added and the same sign is placed.
Different signs are subtracted and the major sign is placed.
[tex]3b ^ 2p-9bp ^ 2 + 9bp[/tex]
Answer:
The simplified expression is:
[tex]3b ^ 2p-9bp ^ 2 + 9bp[/tex]